The period prevalence of double expression diffuse large B-cell lymphoma patients and its associated risk factors and treatment response in Hospital Universiti Sains Malaysia from 2004 to 2015 - Yong, Teh Chee (2017)
Background and Objective: Diffuse Large B-Cell Lymphoma (DLBCL) is a heterogeneous and complex disease. Its protein expression of MYC and BCL2 and/or BLC6 (Double Expression) is associated with poor response to standard treatment, thus poor prognosis. The aim is to determine the period prevalence of Double Expression phenotype in DLBCL patients and also its associated risk factors and treatment response Methods: We performed a retrospective record review involving adult DLBCL patients from 2004 to 2015 in Hospital Universiti Sains Malaysia. Demographic, clinical and laboratory information were extracted from medical record, whereas double expression status was extracted from histopathology department database. Results: A total of 27 DLBCL patients were recruited in this study. The period prevalence of Double Expression Phenotypes was 59.3%. It was not significantly associated with early response during interim assessment (p=0.182); but was significantly associated with non-complete responserate toward RCHOP regimen (p=0.002). It only significantly associated with serum LDH level (p=0.015). There was no significant association between age, gender, ethnicity, stages, B symptoms, ECOG status, revised IPI, Extra-nodal, CNS and bone marrow involvement with Double Expression phenotype. Conclusion: The period prevalence of Double Expression Phenotypes was 59.3%. Patients with Double Expression Phenotypes were associated with lower chance to achieve Complete Response with RCHOP regimen. Among the selected variables, raised serum LDH remained the significant factor associated with Double Expression Phenotypes.